Answer:
x = -1 and x = 7
Step-by-step explanation:
2x^2 + 2x - 14x - 14
2x^2 - 12x -14
Divide through by 2 to simplify the expression
x^2 - 6x - 7
x^2 - 6x -7
Now, let's think of two numbers that when added up gives -6 and when multiplied gives -7
Yes! It's -7 and +1
-7 + 1 = -6 , and -7* 1 = -7
Now, lets substitute these numbers in the expression
x^2 -7x + x - 7
factorize
x(x - 7) + 1(x - 7)
(x + 1) (x - 7)
Now equate to zero
(x + 1) (x - 7) = 0
x + 1 = 0
subtract 1 from both sides
x +1 - 1 = 0 -1
x = -1
Also,
x - 7 = 0
Add 7 to both sides
x -7 + 7 = 0 + 7
x = 7
Hence, x = -1 and x =7
Answer:
4x+6
Step-by-step explanation:
x-5+(3x+11)=4x+6
Variable: a symbol for a number you don’t know yet
inequality: 60=22+8x
Answer: 30 goldfish
Step-by-step explanation: Bruce has 18 goldfish. If Isabelle has 5 times as many goldfish as Bruce she will have 18*5=90 goldfish. If Arlene has 1/3 times as many goldfish as Isabelle she will have 90/3=30 goldfish.